2016
DOI: 10.4052/tigg.1416.1e
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles and Possible Roles of Galectins in the Corpus Luteum

Abstract: Galectins, β-galactoside binding lectins, are involved in various physiological and pathological events. The corpus luteum (CL) is a transient endocrine tissue that produces large amounts of progesterone, which is essential for a successful pregnancy, and stagespecifically expresses galectin-1 and galectin-3. We herein summarized current knowledge on galectins in the CL of mice, cows, and women in order to clarify the expression profiles, regulatory mechanisms, and possible roles of galectins in the CL of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…LGALS1 gene encodes Gal1, one of 15 members of a family of β-galactoside-binding proteins called galectins, which are described to function as homodimeric proteins consisting of 14.5 kDa subunits. Gal1 expression is regulated via the luteinizing hormone/choriogonadotropin receptor (LHCGR), a common receptor for LH and hCG [ 19 ]. Interestingly, hCG stimulation in hGL5 cells stimulated intracellular accumulation of cAMP in hGL5 cells [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…LGALS1 gene encodes Gal1, one of 15 members of a family of β-galactoside-binding proteins called galectins, which are described to function as homodimeric proteins consisting of 14.5 kDa subunits. Gal1 expression is regulated via the luteinizing hormone/choriogonadotropin receptor (LHCGR), a common receptor for LH and hCG [ 19 ]. Interestingly, hCG stimulation in hGL5 cells stimulated intracellular accumulation of cAMP in hGL5 cells [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that the corpus luteum, which produces progesterone for the establishment and maintenance of pregnancy, stage-specifically produces galectin-1 and -3 in mice, cows, and women, suggesting their involvement in the regulation of luteal function (17). Changes in galectin expression during the estrous cycle are also observed in other parts of the female reproductive tract, including the oviduct, uterus, and vagina, indicating that ovarian steroids regulate galectin expression in these organs (6).…”
Section: Galectins In the Reproductive And Endocrine Systemsmentioning
confidence: 99%
“…Galectin-1 expression in luteal cells is induced by luteotrophic LH, hCG, and PGE, while the mechanisms regulating The cellular expression of galectins correlates with changes in the glycan structure. We previously reported that α2,6-si- alylation on the terminal galactose on glycoconjugates, which inhibits galectin-1 binding, negatively correlated with the expression of galectin-1 in luteal cells (17). The differential expression of α2,6-linked sialic acid and galectin-1 has also been observed in cancer cells, and is related to sensitivity to anti-VEGF treatments to inhibit angiogenesis in tumors (33).…”
Section: G What Regulates Galectin Expression?mentioning
confidence: 99%
See 1 more Smart Citation